Understanding crisis therapies : an integrative approach to crisis intervention and post traumatic stress - Loughran, Hilda (Jessica Kingsley Publishers, 2011)
Crisis intervention is a brief therapy and immediate response which aims to support the person through the crisis period. This book covers the different influences on crisis therapies and traces the development of crisis theory across its different phases